Intracellular Streptococcus pneumoniae develops enhanced fluoroquinolone persistence during influenza A coinfection - Hernandez-Morfa, Mirelys; Reinoso-Vizcaino, Nicolas M.; Zappia, Victoria E.; Olivero, Nadia B.; Cortes, Paulo R.; Stempin, Cinthia C.; Perez, Daniel R.; Echenique, Jose (Frontiers in Microbiology, 2024)
S. pneumoniae is a major pathogen responsible for severe complications in patients with prior influenza A virus (IAV) infection. We have previously demonstrated that S. pneumoniae exhibits increased intracellular survival within IAV-infected cells. Fluoroquinolones (FQs) are widely used to treat pneumococcal infections. However, our prior work has shown that S. pneumoniae can develop intracellular FQ persistence, a phenomenon triggered by oxidative stress within host cells. This persistence allows the bacteria to withstand high FQ concentrations. In this study, we show that IAV infection enhances pneumococcal FQ persistence during intracellular survival within pneumocytes, macrophages, and neutrophils. This enhancement is partly due to increased oxidative stress induced by the viral infection. We find that this phenotype is particularly pronounced in autophagy-proficient host cells, potentially resulting from IAV-induced blockage of autophagosome-lysosome fusion. Moreover, we identified several S. pneumoniae genes involved in oxidative stress response that contribute to FQ persistence, including sodA (superoxide dismutase), clpL (chaperone), nrdH (glutaredoxin), and psaB (Mn +2 transporter component). Our findings reveal a novel mechanism of antibiotic persistence promoted by viral infection within host cells. This underscores the importance of considering this phenomenon when using FQs to treat pneumococcal infections, especially in patients with concurrent influenza A infection.